Performance evaluation of WWW conference system for supporting remote mental healthcare education. (14th February 2008) - Sugita, Kaoru; Uchida, Noriki; De Marco, Giuseppe; Barolli, Leonard; , Arjan Durresi
In order to decrease the moving time of mental healthcare specialists, we have developed a WWW conference system, which can provide the communication between mental healthcare specialists and their students. We implemented the prototype system in LAN environment and analysed the performance by changing the frame rate, frame size and number of clients. The experimental results show that system has enough performance in the LAN environment but PCs need a high CPU power to send, receive and display the high quality live videos.